Mechanical properties of composite sandwich structure - Shen, Gong You. (2008)
This report presents a numerical analysis of three-dimensional mechanical properties of metallic honeycomb sandwich structure and gives details of (1) comparison of the numerical results and theoretical resdts for a single honeycomb core; (2) comparison of mechanical properties of a single honeycomb core with face skins between three directions and (3) comparison of the FE results between real models (single honeycomb core with face skins or multiple honeycomb core with face skins) and the equivalent model. All analyses are carried out for static loading in the linear-elastic model.